THE EFFECTIVENESS OF KAHOOT! AS A LEARNING MEDIA IN INCREASING STUDENT INTEREST IN LEARNING OFFICE MANAGEMENT AND BUSINESS SERVICES - Irsy, Rahmadiani; Susanti, Santi; Wahono, Puji (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
One of the most important factors in learning is student interest, using learning media is one technique to encourage student participation and increase their interest towards learning materials. This research aims to test whether or not there are differences before and after the use of Kahoot! learning media on students’ interest in learning. The research method used in this research is experimental quantitative method one group pre-test-post-test design. The data used in this study are primary data by distributing questionnaires that measure interest in learning before treatment (Kahoot!) and after treatment, then the result processed using the IBM SPSS Statistics 20 version. The sample in this study used one class in class XI majoring in Office Management and Business Services (MPLB) at Public Vocational High Schools 48 Jakarta totaling 36 students. The results of the analysis show that there is a significant difference before and after the use of Kahoot! learning media on student interest in learning with a significance level of 5%. So it can be concluded in this study that the use of Kahoot! as a learning media is effective for increasing students’ interest in learning.